O corpo e o trabalho na obra de Simone Weil - Débora Mariz (2016)
Although the demand of the current labor market focus on the service sector and not in the industrial one, unlike the time in which Simone Weil lived, the problem of the meaning of work still arises poignantly. This is because the mechanization of work and the split between thinking and doing acquired another shapes, nonetheless no less oppressive, as we can see in the models of achievement of goals and in the standardization of behavior, like in the telemarketing sector. The alienation at work are still present even today as well the consequences of the civilization of work: the sign of the unlimited in the disproportion, in the imbalance and of the human act. The Weil’s proposal for a civilization of work go beyond the scope of formal relations of production, consisting in a new way to how man should act in the world, in which the body plays a key role. In this sense, the work goes beyond the economic and social dimension, without denying them, acquiring a properly anthropological-philosophical sense. We find among the interpreters of Simone Weil several analyzes about the importance of work in their thinking. However, unlike the notion of “work”, the concept of “body”, except in some papers, not yet received an extensive treatment. Thereby that is the reason to be of our thesis: the defense of the centrality of the body in the Weil´s philosophy. Therefore, we emphasize the importance of work in the thought of S. Weil, seeking to point out the conceptual status of the body in her thinking, understood in its mediating dimension, i.e. as an Archimedean point between necessity and good. Also we elucidated how and by what mechanisms occurs this body habituation, pointing out the concepts of “reading” and “attention” and linking them to a notion of “rhythm”. From this we show how the already habituated body exerts its action in the world, which leads to Weil´s use of the term “non-acting action”, typical of the Hindu and Taoist tradition. Finally, we analyze the possibilities to exercise today the reinterpretation of work proposed by our thinker establishing possible relations between her thought and authors of psychology of work like Yves Clot and Christophe Dejours, as well as with the analysis of the philosopher Hubert Dreyfus about the importance of the body in the acquisition of skills.